2017
DOI: 10.1038/s41588-017-0008-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual-lineage-specific DNA methylation regulates meiosis in Arabidopsis

Abstract: DNA methylation regulates eukaryotic gene expression and is extensively reprogrammed during animal development. However, whether developmental methylation reprogramming during the sporophytic life cycle of flowering plants regulates genes is presently unknown. Here we report a distinctive gene-targeted RNA-directed DNA methylation (RdDM) activity in the Arabidopsis thaliana male sexual lineage that regulates gene expression in meiocytes. Loss of sexual-lineage-specific RdDM causes mis-splicing of the MPS1 gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(182 citation statements)
references
References 52 publications
(32 reference statements)
13
168
0
Order By: Relevance
“…CDKG1 has previously been shown to be involved in the splicing of the CalS5 gene in the tapetal cells affecting pollen fertility (Huang et al ., ). In addition, a recent survey of transcripts in the male sexual lineage has shown that mis‐splicing of the MPS1 gene leads to meiotic defects (Walker et al ., ). Taken together, these observations suggest that splicing is an important regulatory mechanism during meiotic cell divisions.…”
Section: Discussionmentioning
confidence: 97%
“…CDKG1 has previously been shown to be involved in the splicing of the CalS5 gene in the tapetal cells affecting pollen fertility (Huang et al ., ). In addition, a recent survey of transcripts in the male sexual lineage has shown that mis‐splicing of the MPS1 gene leads to meiotic defects (Walker et al ., ). Taken together, these observations suggest that splicing is an important regulatory mechanism during meiotic cell divisions.…”
Section: Discussionmentioning
confidence: 97%
“…However, further analysis of these pathways and their target loci is needed to fully describe their role in meiotic development. One such function has been demonstrated in a recent study by Walker et al (2018) showing that de novo RNA-directed DNA methylation (RdDM) induces cell-lineage-specific epigenetic marks regulating meiotic gene expression in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…However, SHH1-mediated recruitment only accounts for about half of known RdDM loci, suggesting that additional mechanisms of Pol IV recruitment remain to be identified. Other examples of organ-specific RdDM suggest that regulated expression of Pol IV activity, perhaps through tissue-specific epigenetic modification, is an underexplored developmental mechanism Walker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%